Understanding with a Practical Perspective the Corruption Mode of Goods/Services Procurement in Indonesian Public Organizations - Hardinata, Dodi; Hardinata, Auliyah Patih (International Review of Management and Marketing, 2024)
This research aims to clarify the study of corruption in public procurement in public organizations in Indonesia, which when studied through the dimensions of anthropology and democracy is considered too broad in scope and cannot touch the main substance in the discussion of corruption that is specific to public organizations. Corruption in public procurement management in Indonesia is still seen as part of unethical behavior and from a rational perspective is also seen as deviant behavior. The factors for the formation of unethical behavior and categorized as deviant behavior are due to, among others, the structural pressure factors of individuals in public organizations and the intervention factors of parties ranging from vendors, state administrators, and state officials in providing "lure" in the form of gifts or rewards for state administrators and state officials to abuse authority. The results of the study successfully identified modes of corruption in the procurement of goods/services based on the stages and perpetrators of corruption. Corruption in particular in Indonesia is also caused by the weak supervision and management system for preventing corruption in Indonesia. The design of an appropriate and credible public procurement method is one of the solutions to reduce the risk of corruption that begins with the public procurement process. The e-Purchasing method with the e-Cataloque mechanism without negotiations with vendors as a concrete manifestation of the selection of goods/services procurement methods is considered to be very supportive of corruption prevention efforts in Indonesia, because it can directly limit corrupt behavior in public organizations. The novelty, in this study, is to provide recommendations for improvement in the form of a recommendation system design for government procurement of goods/services that is more directed at prioritizing the use of the e-Purchasing method with the e-Cataloque mechanism to reduce the risk of corruption in government spending.